From Filthy to Clean: A Community Service Initiative by KPM POSKO 1 at the Neglected Balai Desa Potoan in Dusun Bujudan, Desa Potoan Daya - Hadi, Rusmawati Hadiniyah; Abroriyah, Hilma; Sam’a, Ulfatus; Hofifah, Hofifah; Kibtiyah, Kibtiyah; Jannah, Faiqotul (Al-Ridha: Jurnal Pengabdian kepada Masyarakat, 2025)
The village hall is a public service building, where it is something that needs to be considered starting from adequate facilities, quality of service, and its environment. The village hall does not meet the standards of eligibility for the community if the environment is not maintained then it will eventually become a source of disease/discomfort for the community. As happened in the Potoan Daya Village Hall which is poorly maintained, filled with grass, and neglected. This study uses a descriptive qualitative approach with field observation, interviews, and documentation as the main techniques for data collection. The results of this study found that after a direct survey, this public community service building is like a building that is no longer inhabited, outdated, the walls are faded, and covered in moss. In the front yard there are many weeds that continue to grow and so much that they cover the bricks. As for the building itself, the front of the building is very dirty and very unsuitable for health services because it is not health that is obtained but will bring disease. Community service by POSKO 1 is a bridge to a beautiful Village Hall.